(untitled) (Iraqi Journal of Medical Sciences, 2024)
Background: Thyroid cancer is the fifth most common cancer in women, worldwide; and the second in Iraqi women according to the statistics of global cancer observatory Iraq fact sheets at 2021. Papillary thyroid carcinoma comprising 90% of thyroid cancers. Annexin A6 is an immunohistochemical marker developed from polyclonal IgG antibody to Annexin A6 protein, which aids in modulating adenosine triphosphate-induced calcium (Ca2+) signaling in thyrocytes. Objective: To evaluate immunohistochemical expression of Annexin A6 in papillary thyroid carcinoma and its correlation with age and sex of patients, stage of cancer and lymph node involvements. Methods: This is a retrospective case control study done at Baghdad, including 30 tissue samples (paraffin block) of papillary thyroid carcinoma, obtained from Al-Yarmouk Teaching Hospital Laboratory and a private laboratory in Baghdad (Dr. Raji Hussein Alhadithi Laboratory) during the period from January 2021 until October 2021. The patients divided into groups according to their age, sex, cancer stage and lymph node involvement, then correlated with Annexin A6 immunohistochemical score of staining. For each sample, 2 serial sections of 4 µm were taken, one stained with Hematoxylin and Eosin and the other stained immunohistochemically with Annexin A6. Results: Annexin A6 expression was positive both membranous and cytoplasmic ??? in (70%) of cases. The intensity was weak in 3 (14.3%), intermediate in 7 (33.3%) and strong in 11 (52.4%) of cases. High, moderate and low expression level was observed in (43%), (38%) and (19%) of patients, respectively. Mean age of patients were 39 years old. Females positive for Annexin A6 represents 77% of patients. Annexin A6 were positive in 75% of patients with lymph node metastasis. Annexin A6 expression more commonly expressed in patient with stage 2 papillary thyroid carcinoma (80% of them). Conclusion: Annexin A6 is highly expressed in thyroid tissue with papillary thyroid carcinoma. No significant correlation between Annexin A6 and any of clinicopathological parameter. Keywords: Annexin A6, ANXA6, papillary thyroid carcinoma, tumor progression Citation: Aziz ZM, Ahmed BS. Immunohistochemical evaluation of Annexin A6 in papillary thyroid carcinoma: A clinicopathological study. Iraqi JMS. 2024; 22(1): 54-64. doi: 10.22578/IJMS.22.1.7